Ekonomické aspekty sportovního klubu - Vrbata, Josef, 1960- (2007)
AutordiplomovepraceBcJosefVrbataNazevdiplomovepraceEkonomickeas pektysportovnihoklubuObsahdiplomovepracepraceanalyzujeprostredi sportovniorganizaceastanovujepostupykezlepsenijejihospodarskesi tuaceMistozpracovanidiplomovepraceTrutnovRokzpracovani2007Pocet stran64.